Not your typical strip mall - Matthew Hufft (Oz, 2010)
The field of progressive architecture and the role of the socially responsible architect are both evolving at a dramatic rate. It is virtually impossible to predict how the profession will transform itself due to rapid advancements in sustainable technologies, materials, systems, and contractual relationships.